Elaboration of a case report or review paper in the methodology for research in medicine subject - Aguilar-Vargas, Esteban (2017)
Introduction: In medical education, it is important to train students in scientific writing and research methods, relevant for progress of health sciences. The curriculum for the undergraduate program of medical education at the Marista University of Merida, Yucatan, Mexico, includes the subject of research methodology in the sixth semester, and currently involves the generation of skills for written communication. In this article, we present the results obtained in the academic program of the research methods course, in which the students develop a draft of an academic article and subsequently an original article consisting of a clinical case report or a review article. Methods: Descriptive, observational study obtained from a survey applied to the students. Additionally, we discuss on the academic products derived from the course that were submitted for publication, six months after the commencement of the course; we also discuss the experiences and perceptions expressed by the students. Results: From 60 students, 19 (32%) opted for writing a clinical case report and 41 (68%) for a review paper. To this day one article derived from the material has been published, and two review papers and three clinical cases are currently under peer review. Conclusions: Undergraduate students were able to develop review manuscripts and clinical case reports of quality and to choose them taking into account access to the data, the time required and the structure of the manuscript.